Effects of (MHD) and wall properties oscillatory flow for williamson fluid with constant viscosity through porous channel - A.N.ALSAFI, Zain Alabdeen; Al-Aridhee, Ahmed A.H.; Al-Waily, Saif Razzaq (Wasit Journal of Computer and Mathematics Science, 2021)
In this research, the williamson flow with heat transfer through the tube of compliant wall properties with slip at boundaries is analyzed analytically. An approximated theoretical model is constructed of springbacked flexible compliant walls pipe, chosen to move as sinusoidal wave
Keywords: Wall properties; Heat transfer; williamson flow